Impact of Superparamagnetic Iron Oxide Nanoparticles on THP-1 Monocytes and Monocyte-Derived Macrophages - Polasky, Christina; Studt, Tim; Steuer, Ann-Kathrin; Loyal, Kristin; Lüdtke-Buzug, Kerstin; Bruchhage, Karl-Ludwig; Pries, Ralph (Frontiers in Molecular Biosciences, 2022)
Superparamagnetic iron oxide nanoparticles (SPIONs) are currently under examination for magnetic particle imaging, which represents a radiation free technology for three-dimensional imaging with high sensitivity, resolution and imaging speed. SPIONs are rapidly taken up by monocytes and other phagocytes which carry them to the site of inflammation. Therefore, the SPION biocompatibility is an essential parameter for a widespread MPI usage. Many improvements are expected from SPION development and its applications for cell visualization, but the impact of MPI optimized dextran coated SPIONs on the cellular characteristics of monocytic cells has been poorly studied up to now. THP-1 monocytes, monocyte-derived macrophages (MDM) as well as peripheral blood monocytes were incubated with MPI-optimized dextran-coated SPIONs of a size between 83.5 to 86 nm. SPION uptake was measured by FITC fluorescence of labeled SPIONs and Prussian blue staining. The activation of monocytes and MDMs was evaluated by CD14, CD11b and CD86 in flow cytometry. The secretion of IL-1β and IL-10 was analyzed in supernatants. SPIONs were rapidly taken up by monocytes and monocyte-derived macrophages while no decrease in cell viability was observed. Expression patterns of CD11b, CD14 and CD86 were not affected in THP-1 monocytes and MDMs. Monocyte differentiation in macrophages was hindered during SPION uptake. THP-1 monocytes as well as monocyte-derived macrophages showed significantly increased IL-1β and decreased IL-10 secretion by tendency after SPION treatment. Dextran-coated SPIONs showed a low cytotoxicity on monocytes but exert undesirable inflammatory side effects that have to be considered for imaging applications.